Field Day 2005 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Each Field Day report consists of individual research reports on topics specific to the region, including cultural methods for most of the major crops grown in Kansas, mitigating the effects of weeds, insects, and disease associated with those crops, and irrigation. Research is conducted and reports written by staff of the K-State Research and Extension Southwest Research Extension Center.
Keywords: Kansas; Weather; Crops; Tillage systems; Water management; Weeds; Insect biology and control